Analysis of Factors Affecting the Performance of State Civil Apparatus (ASN) in the Semarang City Government Environment - Reta, Selly Aisya (Generasi Sains Indonesia, 2024)
This study examines the factors influencing the performance of State Civil Apparatus (ASN) in the Semarang City Government environment. Using a quantitative approach, the research investigates how leadership styles, motivation, work environment, and career development opportunities impact ASN performance. The results show that leadership style is the most significant factor, followed by motivation, with both significantly affecting the work performance of ASN. The work environment and career development, though important, were found to have a lesser but still notable influence. These findings align with existing literature suggesting that leadership, employee motivation, and a positive work environment are essential for improving public sector productivity. The study provides recommendations for enhancing ASN performance by focusing on leadership development, improving job satisfaction, and providing more career growth opportunities.